2021
DOI: 10.3389/fgene.2021.638217
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Function of PURA and Its Implications in Neurological Diseases

Abstract: In recent years, genome-wide analyses of patients have resulted in the identification of a number of neurodevelopmental disorders. Several of them are caused by mutations in genes that encode for RNA-binding proteins. One of these genes is PURA, for which in 2014 mutations have been shown to cause the neurodevelopmental disorder PURA syndrome. Besides intellectual disability (ID), patients develop a variety of symptoms, including hypotonia, metabolic abnormalities as well as epileptic seizures. This review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 142 publications
(256 reference statements)
3
30
0
Order By: Relevance
“…Consistent with a nuclear role of PURA, we do observe binding of PURA to nuclear RNAs such as NEAT1 and MALAT1 . The minor fraction of PURA in the nucleus might be involved in transcriptional regulation as reported previously (3,15). While this might be one of PURAs functions, it was subsequently shown to associate with cellular RNAs and to bind single-stranded DNA and RNA sequences in vitro in the same way and with similar affinities (23).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with a nuclear role of PURA, we do observe binding of PURA to nuclear RNAs such as NEAT1 and MALAT1 . The minor fraction of PURA in the nucleus might be involved in transcriptional regulation as reported previously (3,15). While this might be one of PURAs functions, it was subsequently shown to associate with cellular RNAs and to bind single-stranded DNA and RNA sequences in vitro in the same way and with similar affinities (23).…”
Section: Discussionsupporting
confidence: 71%
“…In recent years, an increasing number of RNA-binding proteins have been implicated in the pathology of human disorders, in particular in neuronal diseases (1,2). One of them is the purine rich element binding protein A (PURA, formerly known as Puralpha) (3). In 2014, mutations in the PURA gene have been linked to the neurodevelopmental disorder PURA Syndrome (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…For example, deletions of the PURA gene cause PURA syndrome, a neurodevelopmental disorder. There is also evidence demonstrating Pur-alpha can associate with RNAs including NEAT1 and C9orf72 repeat expansions, and it can be incorporated into stress granules [further reviewed in (Molitor et al, 2021)]. Recently, Daigle et al identified Pur-alpha in stress granules derived from FUS-ALS patients and, upon shRNA-mediated knockdown in HEK293T cells, prevented stress granule formation, suggesting Pur-alpha may be able to regulate FUS LLPS (Daigle et al, 2016).…”
Section: Pur-alphamentioning
confidence: 99%
“…Evolution has tagged this genomic region as inalterable, which may prove its unique and essential role in interacting with DNA and RNA molecules. It has been reported that any mutation in the PURA protein causes the full spectrum of the human PURA syndrome [ 53 ].…”
Section: Discussionmentioning
confidence: 99%